First report of Cactodera milleri Graney and Bird, 1990 from Colorado and Minnesota - Skantar, Andrea M. (J Nematol, 2021)
In 2019, Cactodera milleri cysts were discovered from soil samples collected from a Chenopodium quinoa field, located in Mosca, Alamosa county, Colorado, USA. Approximately 200 lemon shaped cysts and several hundred juveniles were recovered from the affected quinoa plants. The same species was also identified from several counties in Minnesota from samples submitted over the years by the Minnesota Department of Agriculture as part of the Animal and Plant Health Inspection Service (APHIS) efforts to survey states for the presence of Pale Potato Cyst Nematode. The cysts and juveniles (J2) were recovered from soil samples through sieving and Baermann funnel extraction. The nematode species was identified by both morphological and molecular means as Cactodera milleri (Graney and Bird, 1990). To our knowledge this represents the first report of Cactodera milleri from Colorado and Minnesota.